a t (a+b) ² = a² + b²+2ab (a-b)²= a²+b²-2ab (a+b) (a-b) = a² -b² (x+a) (x+b) = x² +(a+b)x+ab ​

Question

a t
(a+b) ² = a² + b²+2ab
(a-b)²= a²+b²-2ab
(a+b) (a-b) = a² -b²
(x+a) (x+b) = x² +(a+b)x+ab

in progress 0
4 weeks 2021-09-21T23:43:41+00:00 2 Answers 0 views 0

Answers ( )

  1. Ava
    0
    2021-09-21T23:44:48+00:00

    Answer:

    kya kr na hai is question me please tell

    0
    2021-09-21T23:45:12+00:00

    Answer:

    what is the question dude

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )